Effect of Harvest Years on Chemical Composition of Essential Oil of Bitter Fennel (Foeniculum vulgare subsp. piperitum) Leaves - Figueredo, Guilles; Claude Chalchat, Jean; Y. Al Juhaimi, Fahad; Musa Ozcan, Mehmet (Asian Journal of Chemistry, 2012)
The essential oils of leave of Foeniculum vulgare subsp. piperitum (Apiaceae) growing wild in south Anatolia, Turkey were extracted by hydrodistillation and analyzed by GC and GC-MS. The percentage yields of the essential oils from leaves of bitter fennel harvested in different years (from 2003 to 2008) were 1.3, 3.09, 2.1, 1.95, 1.7 and 1.9 %, respectively. The major constituents varied depending on harvest years. Methyl chavicol, fenchone, limonene and fenchyl acetate (exo) were established as the major components of bitter fennel leaves collected in different years. The main constituents of leave oil were methyl chavicol (24.67-69.93 %), fenchone (7.82-14.50 %), limonene (2.39-9.85 %) and fenchyl acetate (exo) (0.17-14.21 %) among the years.